Disseminated Mycobacterium interjectum Infection with Bacteremia, Hepatic and Pulmonary Involvement Associated with a Long-Term Catheter Infection. (18th January 2017) - Sotello, David; Hata, D. Jane; Reza, Mohammed; Satyanarayana, Raj; Arunthari, Vichaya; Bosch, Wendelyn
Abstract : We present a 49-year-old female with one year of intermittent fevers, chills, night sweats, and significant weight loss. Liver and lung biopsy showed evidence of a granulomatous process. Blood and liver biopsy cultures yielded growth of presumed Mycobacterium interjectum, thought to be related to a disseminated long-term central venous catheter infection. She successfully received one year of combined antimicrobial therapy after catheter removal without recurrence of disease. M. interjectum has been previously described as a cause of lymphadenitis in healthy children and associated with pulmonary disease in adults, although other localized infections have been reported. This is the first case described of a disseminated M. interjectum infection with bacteremia, hepatic and pulmonary involvement associated with a long-term catheter infection.